Epidemiologic pattern and factors associated with adverse outcomes of diabetic ketoacidosis in medical intensive care units of a tertiary care centre in India - Shubhadeep Paul; Sourav Debnath; Anurag Kumar Singh; Shivang Mishra; Sumit Rajotiya; Mahaveer Singh; Rahul Parashar; Pusparghya Pal; Sachin Kumar (Endocrine and Metabolic Science)
Aim: Diabetic ketoacidosis (DKA) is a dreadful complication of diabetes mellitus characterized by a biochemical triad of hyperglycemia, ketosis, and metabolic acidosis. The clinic-epidemiologic pattern and outcomes of DKA in the Indian subcontinent are largely unexplored, yet understanding them is crucial for optimizing management strategies. Methods: A total of 138 patients admitted with a DKA diagnosis were reviewed retrospectively over two years. Patient demographics, clinical history, laboratory findings, precipitating factors, and intensive care management were extracted from case files. Clinical outcomes were classified as either discharge or death. Data analysis was performed using SPSSv29. Results: The mean age of the patients was 41.54 (16) years; 77 (55.79 %) were female, 56.52 % had type 1, 23.19 % had type 2, and 20.29 % had pancreatic diabetes. Non-compliance with infection (21.02 %), and pancreatitis (21.01 %) were common DKA triggers. Severity was assessed by pH, anion gap, and bicarbonate levels. The overall mortality rate was 11.59 %. Factors significantly associated with mortality included age >60 years, >3 previous DKA episodes, hypokalaemia, elevated serum creatinine, and altered sensorium. Conclusion: These findings emphasize the importance of demographics and risk factors in assessing DKA mortality risk, aiding early identification and targeted interventions for high-risk patients.